2008
DOI: 10.1037/a0014451
|View full text |Cite
|
Sign up to set email alerts
|

How expressions of forgiveness, purpose, and religiosity relate to emotional intelligence and self-concept in urban fifth-grade students.

Abstract: This study investigated how the tendency to express forgiveness, purpose, and religiosity in a free-response essay relates to emotional intelligence and self-concept in 89 5th-graders (mean age = 10.84 years) from an urban public school district in New Jersey. Readers coded essays for expressions of forgiveness, purpose, and religiosity using originally developed rubrics. These data were compared with self-reports on scales of emotional intelligence and self-concept. It was hypothesized that expressions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
1
2
0
1
Order By: Relevance
“…Like this study in Ellen Pack’s study, potential effect of religion on positive EI changes of Christians was proved ( 31 ). According to Elias and Van Dyke, additionally, there is a direct and significant relationship between positive religious orientation and higher EI levels ( 32 ), which was aligned with this study. Belief in existence of the Almighty God and His supreme controlling power can desirably reduce stress levels and grant an unrivalled spiritual power to human beings ( 33 ).…”
Section: Discussionsupporting
confidence: 88%
“…Like this study in Ellen Pack’s study, potential effect of religion on positive EI changes of Christians was proved ( 31 ). According to Elias and Van Dyke, additionally, there is a direct and significant relationship between positive religious orientation and higher EI levels ( 32 ), which was aligned with this study. Belief in existence of the Almighty God and His supreme controlling power can desirably reduce stress levels and grant an unrivalled spiritual power to human beings ( 33 ).…”
Section: Discussionsupporting
confidence: 88%
“…It was suggested that relationship between religiosity and EI tend to be unstable; Van Dyke and Elias [41] reported negative correlation between religiosity and self-reported EI, whereas, Łowicki and Zajenkowski [42] suggested that religiosity was positively correlated with ability EI but not trait EI. However, by applying the religious orientation concept of Allport and Ross [39], there seems to be a consistent finding on the relationship between religious orientation and EI.…”
Section: Introductionmentioning
confidence: 99%
“…Many qualitative methods could provide eclectic and creative means to study different modes of children's spiritual consciousness and experience, including the intuitional marked by nonverbal, nonlinear processes. Children may experience transcendental feelings while dancing (Bond & Stinson, 2000) and engage in spiritual reflection while reading picture books (Kendall, 1999); they also may reflect on religious themes in their personal writing (Van Dyke & Elias, 2008). Thus, social scientists may benefit from moving beyond their comfort zones and reach out to artists, dancers, and musicians to discover novel ways to explore, assess, and enhance children's religiosity and spirituality.…”
Section: Discussionmentioning
confidence: 99%